DO POLITICS: "OFF YOUR DUFFS, YOU EDUCATORS LN THE ARTS! VOU HAVE NOTHLNG TO LOSE BUT CHAGRIN." - Townsend, Richard (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1980)
For those who practise an art - and teaching itself is said to be one - the world of politics of education may seem peculiarly repugnant. There issues are discussed and settled in terms and by criteria that are anything but aesthetic. That the issues are also inescapable does not cut much ice with many artists and teachers, who consequently can appear indifferent to their being settled. Townsend, in all sympathy, here offers a reviving slap to their faces. He reminds them that even in their refusal to discuss their own decisions as teachers, they are taking a political stance; for these decisions affect others. Pointing out that the future of educational funding gets progressively darker as society gets predominantly older, he outlines in shrewd detail three different ways of meeting the urgent threat to art education. Two are recognizably familiar from the antics of others in the contemporary scene; the third and for him preferred scenario points the way to an unexpected and hopeful outcome both for the arts and the humanities in general education. RÉSUMÉ À ceux qui exèrcent un art (et l'on dit de l'enseignement que c'en est un), l'expression "politique de l'éducation" peut sembler particulièrement répugnante. On discute de ces questions et on les règle généralement en des termes et selon des critères qui n'ont rien d'esthétique. Le fait que ces questiom soient inéluctables n'impressionne ni les artistes ni les enseignants qui peuvent ansi paraître indifférents à leur règlement. Townsend, en toute sympathie, leur assène ici une bonne gifle rafraîchissante. Il leur rappelle que leur refus même de discuter de leur propres décisions en tant que professeurs est un geste politique, car ces décisions en affectent d'autres. Soulignant que l'avenir des subventions d'enseignement s'assombrit à mesure que la société vieillit, il propose avec force détails trois solutions pour faire face à la menace qui pèse sur l'enseignement des disciplines artistiques. Deux sont aisément identifiables par rapport à la situation actuelle: le troisième scénario, qui est son préféré, prévoit un avenir très prometteur pour les arts et les sciences humaines dom les programmes d'enseignement général.